Influence of Previous General Anesthesia on Cognitive Impairment: An Observational Study Among 151 Patients - Linassi, Federico; De Laurenzis, Alessandro; Maran, Eleonora; Gadaldi, Alessandra; Spano', Leonardo; Gerosa, Gino; Pittarello, Demetrio; Zanatta, Paolo; Carron, Michele (Frontiers in Human Neuroscience, 2022)
Introduction Preoperative neurocognitive disorder (preO-NCD) is a common condition affecting 14–51. 7% of the elderly population. General anesthesia has already been associated with the one-year post-operative neurocognitive disorder (PostO-NCD), specifically, a deficit in executive function, measured by the Trail Making Test B (TMT-B), but its long-term effects on cognitive function have not been investigated. We aimed to detect preO-NCD prevalence in patients scheduled for cardiac surgery and further investigate the possible role of previous general anesthesia (pGA) in general preoperative cognitive status [measured via the Montreal Cognitive Assessment (MoCA)] and/or in executive functioning (measured via TMT-B). Methods In this observational, prospective study, 151 adult patients scheduled for elective cardiac surgery underwent MoCA and TMT-B. Data on age, education, pGA, comorbidities, and laboratory results were collected. Results We discovered a general cognitive function impairment of 79.5% and an executive function impairment of 22%. Aging is associated with an increased likelihood (OR 2.99, p = 0.047) and education with a decreased likelihood (OR 0.35, p = 0.0045) of general cognitive impairment, but only education was significantly associated with a decreased likelihood (OR 0.22, p = 0.021) of executive function impairment. While pGA did not significantly affect preO-NCD, a noteworthy interaction between aging and pGA was found, resulting in a synergistic effect, increasing the likelihood of executive function impairment (OR 9.740, p = 0.0174). Conclusion We found a high prevalence of preO-NCD in patients scheduled for cardiac surgery. General cognitive function impairment is highly associated with advancing age (not pGA). However, older patients with at least one pGA appeared to be at an increased risk of preO-NCD, especially executive function impairment, suggesting that TMT-B should be associated with MoCA in the preoperative cognitive evaluation in this population.